Implications of EndSARS Protest on National Security and Development - Unachukwu, Daniel; Ezewudo, Ugochukwu Obumneme (International Journal of Law and Public Policy (IJLAPP), 2024)
The EndSARS protest, which was sparked by public outcry against police brutality, had a significant impact on Nigeria’s national security and development. The protest primarily called for the dissolution of the Special Anti-Robbery Squad (SARS), a unit notorious for its human rights abuses. Underlying issues such as poor governance, rampant corruption, and the Federal Government's failure to reform the Nigerian police system were key factors leading to the massive demonstrations in 2020. Citizens were frustrated with the systemic negligence and lack of accountability, which prompted them to demand justice and police reforms. This paper adopts a descriptive approach to analyze the situation and highlights the importance of the government taking proactive measures to address security issues. The protesters’ grievances reflect a broader societal need for transparency, accountability, and fairness in governance. Therefore, it is crucial for the Federal Government to listen to the voice of the people and implement reforms that ensure the protection of citizens' rights and improve police conduct. By addressing these concerns, the government can help prevent the recurrence of such protests, which may escalate into more dangerous and widespread movements in the future. The paper argues that if the underlying factors are left unchecked, future protests could have far more severe consequences for national stability and development. Thus, the government must act decisively to reform the system and restore public trust.